FORMULASI BESARAN PENGANGGARAN BELANJA OBAT DAN BAHAN MEDIS HABIS PAKAI BERDASARKAN POLA MORBIDITAS (Studi Kasus Pada Puskesmas X Kabupaten Y) - Subekti, Firlana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The study aims to describe the budgeting formulation of drugs and consumable medical materials based on morbidity patterns, identify the ratio between morbidity-based budgeting of drugs and consumable medical materials and the budgeting plan proposed by the community health center (Puskesmas) to the Ministry of Health, and determine if the morbidity pattern can provide an overview on the need of drugs and consumable medical materials in the future year. This quantitative descriptive research is carried out at Puskesmas X in X District. The formulation is administered by classifying the drugs and consumable medical materials based on the type of disease, calculating the morbidity, estimating the use of drugs and consumable medical materials for the comingÂ year, calculating the rest of inventory and safety stocks, and counting the value of drugs and consumable medical materials procurement budget for the year concerned. The result of the study shows that morbidity-based budgetting produces greater value than the current budgeting plan, as indicated in the use of the consumption method implemented by Puskesmas X. This study also confirms that the determination of safety stock policies has a significant effect on the budgeting value.Keywords: Drugs and consumables medical materials; Morbidity; Budgeting